EARNINGS MANAGEMENT AND FIRM SIZE: AN EMPIRICAL ANALYZE IN ALBANIAN MARKET - Llukani, Teuta (European Scientific Journal, ESJ, 2013)
Many studies show the importance of the “earning management and its implications” and are focused mainly in developed countries. Only a few of them analyses this phenomenon in emerging countries or developing economies as it’s the case of Albania. This study aims to:  bring evidence and analyze earnings management initiatives in Albanian context,  identify the relationship between earnings management and firm size,  provide some conclusion with regard to earnings management. Log of total assets is used as proxy for firm size, and absolute value of discretionary accruals for earnings management. Jones Model is used for calculation of discretionary accruals. The results show that firms in the Albanian market are engaged in earnings management initiatives and there are no significant differences concerning earnings management initiatives and practices, comparing large and small size companies.